A World Overview of the Organic Rankine Cycle Market. (September 2017) - Tartière, Thomas; Astolfi, Marco
Abstract: The Organic Rankine Cycle (ORC) technology is a reliable way to convert heat into electricity, either for renewable energy applications (biomass, geothermal, solar), or industrial energy efficiency. ORC systems range from micro-scale (a few kW) for domestic cogeneration to large multi-megawatt geothermal power plants. After a slow initial start, the technology has experienced a much stronger development since the 1970s, mainly because of economic incentives and surging energy prices. However, the large range of applications, manufacturers, and countries make it hard to track the evolution of the technology over the world. Information about more than 700 projects has been collected, cross-validating 27 manufacturers' data with publications and testimonies, allowing to build the first reliable and exhaustive database of ORC plants. As a result, this work analyses the evolution of the ORC market over the years, with today 2.7 GW of cumulated installed capacity. After introducing the ORC technology with a focus on its history, working principle and main applications, the current state and the new trends of the ORC market are presented with a detailed analysis of each application. The evolution of each market is discussed considering the present installed capacity, historical data and macro-economic trends. Finally, future perspectives and growth potential of the ORC market are evaluated, with a special focus on Waste Heat Recovery applications.